Immunohistochemical expression of SPARC in odontogenic keratocysts: a comparative study with other odontogenic cysts - Sopee Poomsawat; Sirada Choakdeewanitthumrong; Sirima Sanguansin; Ounruean Meesakul; Theerachai Kosanwat (BMC, 2024)
Abstract Background Secreted protein acidic and rich in cysteine (SPARC) has been shown to modulate aggressive behavior in several benign and malignant tumors. Little is known about SPARC expression in odontogenic keratocyst (OKC), an odontogenic cyst with an aggressive nature. To the best of our knowledge, only one study has been investigated the expression of this protein in OKCs. This study aimed to characterize SPARC expression in OKCs. Additionally, to determine whether SPARC is associated with aggressive behavior in OKCs, SPARC expression in OKCs was compared with radicular cysts (RCs), dentigerous cysts (DCs) and calcifying odontogenic cysts (COCs). These odontogenic cysts showed no or less aggressive behavior. Methods SPARC expression was evaluated in 38 OKCs, 39 RCs, 35 DCs and 14 COCs using immunohistochemistry. The percentages of positive cells and the intensities of immunostaining in the epithelial lining and the cystic wall were evaluated and scored. Results Generally, OKCs showed similar staining patterns to RCs, DCs and COCs. In the epithelial lining, SPARC was not detected, except for ghost cells in all COCs. In the cystic wall, the majority of positive cells were fibroblasts. Compared between 4 groups of odontogenic cysts, SPARC expression in OKCs was significantly higher than those of RCs (P < 0.001), DCs (P < 0.001) and COCs (P = 0.001). Conclusions A significant increase of SPARC expression in OKCs compared with RCs, DCs and COCs suggests that SPARC may play a role in the aggressive behavior of OKCs.